Texts : contemporary cultural texts and critical approaches - Childs,Peter (Edinburgh University Press, 2006)
Introduction: Starting Points; 1. Film: The Matrix and The I-pod; Approach: Cyberphilosophy; 2. Building: Shopping in Utopia; Approach: Spatial Criticism; 3. Movie Poster: Alien Nature; Approach: Ecocriticism; 4. Pop video: Michael Jackson's 'Thriller' and 'race'; Approach: 'Race' Studies; 5. Celebrity: Diana and Death; Approach: Trauma Theory; 6. TV show: Big Brother after the big Other; Approach: Performativity Theory; 7. Newspaper article: The Gulf War in Real Time and Virtual Space; Approach: Hyperreality; 8. Photograph(er): Cindy Sherman and the Masquerade; Approach: Feminism; 9. Political speech: Margaret Thatcher's Hymn at the Sermon on the Mound; Approach: Historicism; 10. Critical text: Alan Sokal's Sham Transgression; Approach: Reading Postmodernism; 11. Popular novel: The Ethics of Harry Potter; Approach: Ethical Criticism; 12. Short story: Barthelme's Balloon and the Rhizome; Approach: Deleuzian Criticism; 13. Lyric: 'Where's my Snare?': Eminem and Sylvia Plath; Approach: Psychoanalytic Criticism; 14. Autobiography: Martin Amis's Experience; Approach: Self-Life-Writing; 15. Virtual text: Amazonian Democracy; Approach: Globalization Studies; 16. World media event: It's About Time: Cultural History at the Millennium; Approach: Cultural Studies.